A Spatial Segregation : The Existence of Wara Wiri Suroboyo and Conventional Angkot in Gidden’s Structuration Perspective - Khuzaimah; Harrel Ciddan; Nur Khairun Nisa; Hanif Abdurahman Siswanto (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
Surabaya as a big city cannot be separated from the polemic of congestion in every corner of the city. This is caused by the excessive use of private transportation. The congestion led the government to launch wira wiri Suroboyo to increase public interest in riding public transportation. However, the emergence of wira wiri suroboyo has also caused pros and cons in the community, especially in conventional angkot groups. This phenomenon makes researchers interested in conducting research on the process of spatial segregation that occurs with the existence of conventional angkot and wara wiri suroboyo. The method used is qualitative with data collection techniques in the form of observation and interviews. The data was analyzed using miles and hubermans analysis techniques and Anthony Giddens' structuration theory. The results of the study show that there is a structuration process between conventional angkot drivers and the government management of wara wiri Suroboyo. The segregation of work space that occurs is then overcome by the government with various agreements so as not to cause a process of struggle for work space between conventional angkot drivers and wara wiri Suroboyo.